ATMPH 2020
DOI: 10.36295/asro.2020.231131
|View full text |Cite
|
Sign up to set email alerts
|

Studying the impact of vitamin D deficiency in Iraqi acromegalic patients and its relation with some biochemical parameters

Abstract: Acromegaly is described as a less common chronic disease occursas a result ofover secretion of growth hormone (GH) often from a pituitary adenoma; it is connected to noticeable morbidity and increased mortality. Our study aimed to determine calcium (Ca) and vitamin D status inacromegalic patients regarding disease activity and estimating the relationship between vitamin D, IGF-1 and some biochemical parameters. Correlations of vitamin D with IGF-1, BMI, Ca, GOT, GPT, ALP, T3, T4, TSH, urea and creatinine were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(41 reference statements)
2
0
0
Order By: Relevance
“…This increase was explained by the favorable correlation between body weight and bone mineral density rather than obesity. Abdullah et al [30] observed that BMI was considerably greater in ACRO patients when compared to the control group, which is consistent with our findings. Table 2 illustrates that ARG activity was significantly p˂0.0001 decreased in the ACRO patients 3.45±1.30 compared to control 5.98±2.39.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This increase was explained by the favorable correlation between body weight and bone mineral density rather than obesity. Abdullah et al [30] observed that BMI was considerably greater in ACRO patients when compared to the control group, which is consistent with our findings. Table 2 illustrates that ARG activity was significantly p˂0.0001 decreased in the ACRO patients 3.45±1.30 compared to control 5.98±2.39.…”
Section: Resultssupporting
confidence: 93%
“…It is wealth to mention that the study of Hameed et al [34] was in agreement with our findings. In the same manner, Hameed et al [35] and Abdullah et al [30] found that IGF-I levels in ACRO patients were higher compared to the control, these studies concur with our results. The present investigation found that FSG levels in the patients group were significantly higher than control.…”
Section: Resultssupporting
confidence: 93%